Influence of copper content on microstructure development of AlSi9Cu3 alloy - Brodarac Zovko Z.; Dolić N.; Unkić F. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Microstructure development and possible interaction of present elements have been determined in charge material of EN AlSi9Cu3 quality. Literature review enables prediction of solidification sequence. Modelling of equilibrium phase diagram for examined chemical composition has been performed, which enables determination of equilibrium solidification sequence. Microstructural investigation indicated distribution and morphology of particular phase. Metallographic analysis tools enable exact determination of microstructural constituents: matrix αAl, eutectic αAl+βSi, iron base intermetallic phase - Al5FeSi, Alx(Fe,Mn)yCuuSiw and/or Alx(Fe,Mn)yMgzCuuSiw and copper base phases in ternary eutectic morphology Al-Al2Cu-Si and in complex intermetallic ramified morphology Alx(Fe,Mn)yMgzSiuCuw. Microstructure development examination reveals potential differences due to copper content which is prerequisite for high values of final mechanical, physical and technological properties of cast products.